In Defense of La Raza The Los Angeles Mexican Consulate and the Mexican Community, 1929 to 1936 - Balderrama, Francisco E. (University of Arizona Press, 1982)
Mexican communities in the United States faced more than unemployment during the Great Depression. Discrimination against Mexican nationals and similar prejudices against Mexican Americans led the communities to seek help from Mexican consulates, which in most cases rose to their defense. Los Angeles's consulate was confronted with the country's largest concentration of Mexican Americans, for whom the consuls often assumed a position of community leadership. Whether helping the unemployed secure repatriation and relief or intervening in labor disputes, consuls uniquely adapted their roles in international diplomacy to the demands of local affairs.